3x(x+3)-6=5x-5

Simple and best practice solution for 3x(x+3)-6=5x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(x+3)-6=5x-5 equation:


Simplifying
3x(x + 3) + -6 = 5x + -5

Reorder the terms:
3x(3 + x) + -6 = 5x + -5
(3 * 3x + x * 3x) + -6 = 5x + -5
(9x + 3x2) + -6 = 5x + -5

Reorder the terms:
-6 + 9x + 3x2 = 5x + -5

Reorder the terms:
-6 + 9x + 3x2 = -5 + 5x

Solving
-6 + 9x + 3x2 = -5 + 5x

Solving for variable 'x'.

Reorder the terms:
-6 + 5 + 9x + -5x + 3x2 = -5 + 5x + 5 + -5x

Combine like terms: -6 + 5 = -1
-1 + 9x + -5x + 3x2 = -5 + 5x + 5 + -5x

Combine like terms: 9x + -5x = 4x
-1 + 4x + 3x2 = -5 + 5x + 5 + -5x

Reorder the terms:
-1 + 4x + 3x2 = -5 + 5 + 5x + -5x

Combine like terms: -5 + 5 = 0
-1 + 4x + 3x2 = 0 + 5x + -5x
-1 + 4x + 3x2 = 5x + -5x

Combine like terms: 5x + -5x = 0
-1 + 4x + 3x2 = 0

Begin completing the square.  Divide all terms by
3 the coefficient of the squared term: 

Divide each side by '3'.
-0.3333333333 + 1.333333333x + x2 = 0

Move the constant term to the right:

Add '0.3333333333' to each side of the equation.
-0.3333333333 + 1.333333333x + 0.3333333333 + x2 = 0 + 0.3333333333

Reorder the terms:
-0.3333333333 + 0.3333333333 + 1.333333333x + x2 = 0 + 0.3333333333

Combine like terms: -0.3333333333 + 0.3333333333 = 0.0000000000
0.0000000000 + 1.333333333x + x2 = 0 + 0.3333333333
1.333333333x + x2 = 0 + 0.3333333333

Combine like terms: 0 + 0.3333333333 = 0.3333333333
1.333333333x + x2 = 0.3333333333

The x term is 1.333333333x.  Take half its coefficient (0.6666666665).
Square it (0.4444444442) and add it to both sides.

Add '0.4444444442' to each side of the equation.
1.333333333x + 0.4444444442 + x2 = 0.3333333333 + 0.4444444442

Reorder the terms:
0.4444444442 + 1.333333333x + x2 = 0.3333333333 + 0.4444444442

Combine like terms: 0.3333333333 + 0.4444444442 = 0.7777777775
0.4444444442 + 1.333333333x + x2 = 0.7777777775

Factor a perfect square on the left side:
(x + 0.6666666665)(x + 0.6666666665) = 0.7777777775

Calculate the square root of the right side: 0.881917104

Break this problem into two subproblems by setting 
(x + 0.6666666665) equal to 0.881917104 and -0.881917104.

Subproblem 1

x + 0.6666666665 = 0.881917104 Simplifying x + 0.6666666665 = 0.881917104 Reorder the terms: 0.6666666665 + x = 0.881917104 Solving 0.6666666665 + x = 0.881917104 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = 0.881917104 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = 0.881917104 + -0.6666666665 x = 0.881917104 + -0.6666666665 Combine like terms: 0.881917104 + -0.6666666665 = 0.2152504375 x = 0.2152504375 Simplifying x = 0.2152504375

Subproblem 2

x + 0.6666666665 = -0.881917104 Simplifying x + 0.6666666665 = -0.881917104 Reorder the terms: 0.6666666665 + x = -0.881917104 Solving 0.6666666665 + x = -0.881917104 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.6666666665' to each side of the equation. 0.6666666665 + -0.6666666665 + x = -0.881917104 + -0.6666666665 Combine like terms: 0.6666666665 + -0.6666666665 = 0.0000000000 0.0000000000 + x = -0.881917104 + -0.6666666665 x = -0.881917104 + -0.6666666665 Combine like terms: -0.881917104 + -0.6666666665 = -1.5485837705 x = -1.5485837705 Simplifying x = -1.5485837705

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.2152504375, -1.5485837705}

See similar equations:

| 5x-x+x=24 | | 5x+3=10x-9 | | g(x)=4(-5)-5 | | 8x-10=2(4x-7) | | 9(x+8)=5(x-(4-x)) | | (2y-(3y-4)+5y-6)+10y=(12y-12)+36 | | 4x^2-65x+64=0 | | 6x+20=8x+6y | | 6a+5a+2a-6= | | (x/y)(100)=-18 | | (x/Y)*100=-18 | | x^5+4x^4-3x^2+x-6=0 | | (3x^2)-14x+16=0 | | Y=ln(5x^2-9x+2) | | (-3x+5y)-(-2x+4y)= | | 23-5x=14+4 | | 6y-22y= | | f(x)=(0.93) | | (10x-5)/5=15 | | -7x-2=49 | | y=3lnx/2lnx | | 5-8z=-11 | | 180-x=165-2(90-x) | | y=1-6x^2 | | 5x+12=-3x+36 | | 10-3x=2.5x | | 7a+6a-11+15-17+20-6a=-7 | | 1/7•7 | | 25x+7.5x^2=0 | | -16t^2+26t=5 | | 2.5x(10-3x)=0 | | h=-16t^2-44t+6 |

Equations solver categories